2021
DOI: 10.1088/1755-1315/934/1/012055
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Organic Matter Content in Water and Sediment in The Coastal Waters of Bengkalis Island, Riau Province

Abstract: Anthropogenic activities in the coastal waters of Bengkalis Island, Riau Province are thought to have increased due to human activities (settlements, ports, agriculture, households and industry). This caused an increase in organic matter in water and sediment in coastal waters. The content of organic matter in water and sediment can be used as an indicator of the quality of coastal waters. The research aimed to analyze the content of organic matter in water and sediment in the coastal waters of Bengkalis Islan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Sidi et al (2019) reported OM and OC in the wetlands of river Gbako at Baddegi. The values reported are 0.44% and 0.95% for OC and OM respectively which is considered as very low base on Reynolds classification (Yoswaty et al, 2021). Farming system and sediments source can result in elevated levels of the OC and OM in sediments (Yu et al, 2022).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Sidi et al (2019) reported OM and OC in the wetlands of river Gbako at Baddegi. The values reported are 0.44% and 0.95% for OC and OM respectively which is considered as very low base on Reynolds classification (Yoswaty et al, 2021). Farming system and sediments source can result in elevated levels of the OC and OM in sediments (Yu et al, 2022).…”
Section: Introductionmentioning
confidence: 92%
“…The sediments OM for the two wetlands are low using Reynolds classification (Simanjuntak et al, 2020). Sediment OM content consists of 5 classes, namely: >35% is considered very high organic matter content; 17% -35% is high organic matter content; 7% -17% is medium organic matter content; 3.5% -7% is low organic matter content (Yoswaty et al, 2021). A correlation of the Physico-chemical parameters of the sediments from the two wetlands showed poor correlation except for the OM and OC which are strongly positively correlated meaning that, OC or OM increases with increasing concentration of OM or OC Figure 3 and Figure 4.…”
Section: Oc and Om In The Sedimentsmentioning
confidence: 99%